Analisis Pelaksanaan Asesmen Nasional Berbasis Komputer (ANBK) Terhadap Literasi dan Numerasi Siswa Kelas V di SDN Ganrang Jawa 1 dan SDI Teamate - St. Nurwafiqah Maghfirah; Andi Mulawakan Firdaus; Hamdana Hadaming (PT. ALHAFI BERKAH INDONESIA, 2023)
The main problem in this study is how the ANBK is implemented on the literacy and numeracy of fifth grade students at SDN Ganrang Jawa 1 and SDI Teamate. This study aims to describe the implementation of the computer-based National Assessment (ANBK) on the literacy and numeracy of fifth grade students at SDN Ganrang Jawa 1 and SDI Teamate.This type of field research uses a descriptive qualitative approach. Research instruments include questionnaires, interview guidelines, and documentation. The sampling technique used Snowball sampling.The results showed that SDN Ganrang Jawa 1 literacy ability reached 1.45 and numeracy reached 1.43 in 2021, in 2022 the students' AKM reached 1.6 literacy skills and 1.57 in numeracy, there was an increase even though the AKM results were still below the minimum competency. While the results of the AKM in SDI Teamate in 2021 literacy skills reached 1.31 and numeration reached 1.42, in 2022 there will be an increase in literacy and numeracy skills, reaching 2.02. (literacy) and 2.34 (numeration), the increase has reached the minimum competency limit.Based on the results of the study it can be concluded that there are differences in numeracy literacy, at SDN Ganrang Jawa 1 and SDI Teamate. The numeracy literacy supporting activities carried out at SDI Teamate in the form of literacy greetings, showed better results compared to the ANBK results obtained at SDN Ganrang Jawa 1 which only used the library and reading corner. This shows that the preparation of literacy and numeracy supporting facilities has an impact on increasing the results of ANBK achievements.